As sócio-espacialidades e ressignificações das cavalgadas – Itaporanga d’Ajuda/SE - Santos, Daniele Luciano (2018)
The variation that occurred since the 1990s in the composition and structure of the cavalcade in Itaporanga d'Ajuda / SE led us to question its manifestation as a traditional and contemporary festive practice. In this context, we had the objective of analyzing the territories of the cavalcade riding in the city by the socio-spatial practices that maintain and propel them. And, as specific objectives we had: i) trace the time line of the cavalcade and their corteje; ii) apprehend the subjects and the relations undertaken for the accomplishment of the yous routes; iii) understand the socio-spatial practices of horseback riders and yours produces; iv) and ascertain the material and symbolic bases of the territories of the cavalcade. To this end, we base the territory on both power in the concrete sense and in the symbolic sense, because we are interested in ascertaining the production and maintenance of cavalcade by power relations and the interests of local political groups. The socio-spatialities of cavalcade were seized and discussed with the help of authors who emphasize the construction of social space and cultural space by organization, significance of production and appreciation of symbolic aspects. We discuss the multidimensionality of the territory by political practices, cultural and economic factors that conduct the cavalcade as a re-signification tradition and determine their territories in Itaporanga d'Ajuda. The research is of qualitative nature when electing the cavalgada phenomenon as object of study, in seeking to understand it through the socio-spatial practices that maintain it and that unfold in the territory. In addition to the bibliographic review, we adopted as methodology the documentary research in websites and newspapers and the field research using observation, conducting interviews, applying questionnaires and photographic records. We discuss and expose the representations and territories of the cavalcade as a popular feast and as a political event. The feast is apprehended as a traditional manifestation that gives meaning and value to the symbolic aspects of the villages. As a political event, although an old practice, was resignified as market practice, as "currency of exchange of political favors.". The feast and the event that takes place in the cavalcades is still distinguished, respectively, by the sense of appropriate patrimony as popular know-how and by the patrimony instituted by legal norms.